Effect of Salt on Biodegradation of Model Alkanes and Crude Oil Saturates by Hydrocarbon-degrading Bacteria - Feng, Yuchi (Université d'Ottawa / University of Ottawa, 2015)
Crude oil leakages often give rise to in situ contamination with both oil and salt. In this study, the biodegradation of model alkanes and of saturated hydrocarbons in whole crude oil by hydrocarbon-degrading bacteria was investigated at different salt (NaCl, KCl, Na2SO4) concentrations. Changes in cell surface hydrophobicity at different NaCl concentrations were also investigated. The results show that with increasing NaCl concentration, the lag phase for strain growth on hydrocarbons was prolonged; however, the total degradation efficiency was not influenced greatly. The formation of different sizes of cell aggregates at different salt concentrations indicated that salt could indirectly influence mass transfer of hydrocarbons from the medium to the interior of the cells. The results also showed that KCl had a less inhibitory effect on biodegradation than NaCl, and changes of Na2SO4 concentration did not greatly affect biodegradation. In addition, cell surface hydrophobicity increased with increasing NaCl concentration when the cultures were grown on hydrocarbons.
Keywords: Salt; Biodegradation; Alkanes; Crude oil